A Pharmacogenetic Study of VDR fok1 and TYMS Polymorphisms and Their Association With Glucocorticoid-Induced Osteonecrosis in Egyptian Children With Acute Lymphoblastic Leukemia - ElHarouni, Dina; Yassin, Dina; Ali, Nesreen; Gohar, Seham; Zaky, Iman; Adwan, Hassan; Sidhom, Iman (Frontiers in Oncology, 2018)
Purpose: Osteonecrosis is a significant toxicity resulting from the treatment of pediatric Acute Lymphoblastic Leukemia. This study aimed to investigate the relationship between vitamin D receptor fok1 and thymidylate synthase gene polymorphisms with the glucocorticoid (GC) induced osteonecrosis (ON) in Egyptian pediatric ALL patients. In addition, to identify the possible association of genetic polymorphisms with other factors such as gender and ALL subtypes. Patients and Methods: A retrospective case-control study was conducted on 102 pediatric ALL patients under the age of 18 who were treated at Children Cancer Hospital Egypt according to St Jude SR/HR total XV protocol. The recruited patients were composed of 51 cases who developed GC-induced osteonecrosis and 51 age- and gender-matched patients who received glucocorticoids but remained osteonecrosis-free (controls). Genotyping of the VDR fok1 and TYMS genes was performed using restriction fragment length polymorphism and conventional PCR respectively. Results: For the total 102 studied patients, the VDR fok1 SNPs frequency distribution were TT (8.8%), CT (34.3%), and CC (56.9%), while the TYMS tandem repeat gene variations were reported as 2R/2R (20.6%), 2R/3R (45.1%), and 3R/3R (34.3%). VDR fok1 and TYMS polymorphic variants showed no association neither with gender; p-values 0.3808 and 0.1503; respectively; nor with ALL subtypes; p-values 0.9396 and 0.6596; respectively. The VDR fok1 polymorphisms showed a significant association with the development of ON; p-value=0.003, on the other hand, TYMS tandem repeats did not show significant impact on osteonecrosis development; p-value= 0.411. Conclusion: This study showed a significant association between the VDR fok1 polymorphism and osteonecrosis. Such clinical pharmacogenetics results would be promising to discuss the possibility of dose adjustments aiming a regimen with the highest efficacy and least toxicity.